ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI EKSPOR KARET ALAM INDONESIA KE BRAZIL - Ahmad Nasyid Mawardi; Tri Endar Suswatiningsih; Arum Ambarsari (AGRIFITIA : Journal of Agribusiness Plantation, 2021)
Rubber in Indonesia became one of the most important commodities which played an important role as a source of mployment for Indonesia pople, in addition to rubber is also a contributor to Indonesia's foreign exchange. In the modern socity era, rubber is a very important matrial in life because a lot of goods are made from rubber. Indonesia is a country exporting rubber to Brazil. The purpose of this research is (1) To find out the factors that increase Indonesia's natural rubber export to Brazil (2) To prdict Indonesia's natural rubber export to Brazil in the next 3 years.Th method used in this research is descriptive methode, while the data collection method is done by noted all the secondary data in the form of times sries from 2001 to 2017. The data analysis methods used multiple linear regression and trend using Forecasting.The results showed that (1) Brazilian GDP sigificantly a affected the volume of Indonesia's natural rubber exports, while the domestic price of natural rubber and the Rppiah to Dollar exchange rate did not affect (2) The volume of Indonesia's natural rubber export to Brazil for 3 years from 2018-2020 showed positive development. This was agreed in 2018 the volume of Indonesia's natural rubber export to Brazil reached 106.803,5 tons, in 2019 it reached 110.29,3 tons and in 2020 it reached 11.005,2 tons.Keywords : Ekspor, Natural Rubber, Brazil